Temperature-responsive mixed core nanoparticle properties determined by the composition of statistical and block copolymers in the core1. Issue 10 (14th March 2015) - Kotsuchibashi, Y.; Ebara, M.; Hoffman, A. S.; Narain, R.; Aoyagi, T.
<x xml:space="preserve">Abstract</x> Mixed core nanoparticles were prepared from self-assembled statistical and block copolymers by controlling the solution temperature. Interestingly, an equal mass of specific statistical copolymers was successfully loaded into block copolymer micelle cores.